∠(aa1) = 180°.∠(ab) + ∠(a1b) = 180° (т.к. они смежные). ∠(a1b) = 180° - 60° = 120°.∠(ac) + ∠(a1c) = 180° (т.к. они смежные). ∠(a1c) = 180° - 30° = 150°, ∠(ab) = ∠(ac) + ∠(cb). ∠(cb) = ∠(ab) - ∠(ac) = 60° - 30° = 30°.
<span>3а+7 </span><span />⩾<span> 7 при а</span>
⩽1 (при условии, что а –
неотрицательное число)
4/5a+9<span> </span>⩾ <span> 9,8 при а </span>⩾1
8,25
+ 1 3/<span>4а </span>⩽<span> 10 при
а </span>⩽1
2,5<span> – 1 1/5</span>a ⩽<span> 2,5 при а </span>⩾1
1) -5/6 + 3/8=-20\24+9\24=-11\24
2) -2 5/7 - 1 3/14=-2 10\14-1 3\14=-3 13\14
<span>(6/35-4/7)-(-1,8-4,3)-5,7=0
1)6\35-4\7=6\35-20\35=-14\35=-2\5=-0.4
2)-1.8-4.3=-6.1
3)-0.4-(-6.1)=-0.4+6.1=5.7
4)5.7-5.7=0</span>
<span>log(0.6, 10) - log(0.6, 6) = log(0.6, 10/6) = log(6/10, 10/6) = -1
По короче:
</span>log ( 10/6 ) по основанию 0.6 = -1